Pengaruh Kepemimpinan Transformasional Dan Komitmen Organisasi Terhadap Kepuasan Kerja Karyawan - Natan, Nurdin (208-7721)
This study discusses the presence of: (1) Influence of Transformational Leadership on Employee Job Satisfaction Morotai Island district. (2) Effect of Organizational Commitment on Employee Job Satisfaction Morotai Island district. The population in this study were employees of Morotai Island district office of regent. In this study using survey method is the method of collecting primary data by asking questions to respondents and data collection tool was a questionnaire with a population of 159 respondents / person. Tests conducted on questionnaires filled out by respondents using tools SPSS version 15.00 for windows.The results of this study concluded that there is a significant relationship between transformational leadership on Employee Job Satisfaction Morotai Island district. And there is a significant relationship between Organizational Commitment on Employee Job Satisfaction Morotai Island district. In this study variables Organizational Commitment of the most dominant influence on Employee Job Satisfaction District Morotai IslandKeywords: Transformational Leadership, Organizational Commitment, Job Satisfaction